A comprehensive review on energy efficiency enhancement initiatives in centrifugal pumping system. (1st November 2016) - Arun Shankar, Vishnu Kalaiselvan; Umashankar, Subramaniam; Paramasivam, Shanmugam; Hanigovszki, Norbert
Highlights: Investigates losses and efficiency enhancement opportunities in pumping system. Presents efficient component selection in pumping system. Suggests energy optimised sizing and dimensioning of piping system. Reviews optimal control and adjustment methods in parallel pumping. Highlights ongoing research and developments for improving pumping efficiency. Abstract: The energy consumption across the globe is increasing at an alarming rate. This has already shown its impact in the depletion of energy sources and environmental issues (global warming, and weakening of the ozone layer). Certainly, this escalating tendency of energy insufficiency will get aggravated in the future. Efficiency enhancement initiatives are considered to be the key solution in reducing the energy utilization and eventually resisting the global environmental impacts. Of the world's total energy generated, pumping systems, especially the centrifugal pumps consume about 20%. Consequently, the primary focus of global energy policy makers is to enhance energy efficiency in pumping systems. As per the literature, remarkable energy savings can be accomplished by controlling the speed of the pumping system using Variable Frequency Drives (VFDs). For this reason, studies and researches focus primarily on VFD control techniques to improve the efficiency of the pumping system. This article also focuses on component selection, and system dimensioning in addition to the control techniques. Comparison of recent research outcomes of energy efficiency improvements in pumping system has been made to provide an insight for future research.